Intractable Diarrhea due to Secondary Gastrointestinal Amyloidosis in a Patient with History of Leprosy - Chyntia Olivia MJ; Tito Ardi; Evy Yunihastuti; Ari Fahrial Syam; Murdani Abdullah (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2008)
Amyloidosis is not a single disease but a term for diseases that share a common feature: the extracellular deposition of pathologic insoluble fibrillar proteins in organs and tissues. In both primary and secondary amyloidosis, the most commonly involved organ system is the gastrointestinal system, with the colon being the most frequently involved organ. A 30 years-old male, complained of diarrhea since 4 months prior to admission. The colonoscopy examination revealed pancolitis, ileitis, and the result from histopathological examination showed chronic destructive ileocolitis with 40-70% amyloidosis of mucosa. The abdominal ultrasonography showed chronic cholecystitis, multiple cholelithiasis and minimally ascites. The esophagogastroduodenoscopy revealed candida esophagitis, erosive pangastritis grade V, pyloring gapping, erosive duodenitis, bile reflux gastritis and esophagitis, and the result from histo-pathological examination showed amyloidosis on gastric mucosa.The immunofixation electrophoresis was negative for monoclonal light chains, and the serum protein electrophoresis showed normal pattern. Enteral and parenteral nutritional therapy were given. Secondary infection was treated by antibiotics. Complication and organ failure occured lately. This chalenging case demonstrated complicated management of gastestinal amyloidosis. Keywords: gastrointestinal amyloidosis, intractable diarrhea, leprosy